2019
DOI: 10.5194/angeo-37-1095-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparing high-latitude thermospheric winds from Fabry–Perot interferometer (FPI) and challenging mini-satellite payload (CHAMP) accelerometer measurements

Abstract: Abstract. It is generally assumed that horizontal wind velocities are independent of height above the F1 region (> 300 km) due to the large molecular viscosity of the upper thermosphere. This assumption is used to compare two completely different methods of thermospheric neutral wind observation, using two distinct locations in the high-latitude Northern Hemisphere. The measurements are from ground-based Fabry–Perot interferometers (FPI) and from in situ accelerometer measurements onboard the challenging mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Thus, even though some overlap between these past missions existed, none of them presented good opportunities for in‐space cross‐comparison/calibration. Their wind observations (mostly upper thermospheric) have been cross‐validated in the past, mostly using ground‐based wind measurements—climatologically as well as using conjunctions (e.g., Aruliah et al., 2019; Dhadly, Emmert, Drob, Conde, et al., 2018; Dhadly et al., 2017, 2019; Duboin, 1997; Gault et al., 1996; Killeen et al., 1984). However, large‐scale neutral wind cross‐validation studies are extremely rare due to the lack of continuous and simultaneous vector wind measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even though some overlap between these past missions existed, none of them presented good opportunities for in‐space cross‐comparison/calibration. Their wind observations (mostly upper thermospheric) have been cross‐validated in the past, mostly using ground‐based wind measurements—climatologically as well as using conjunctions (e.g., Aruliah et al., 2019; Dhadly, Emmert, Drob, Conde, et al., 2018; Dhadly et al., 2017, 2019; Duboin, 1997; Gault et al., 1996; Killeen et al., 1984). However, large‐scale neutral wind cross‐validation studies are extremely rare due to the lack of continuous and simultaneous vector wind measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Aruliah et al. (2019) compared high‐latitude thermospheric winds measured by two ground‐based FPIs and CHAMP accelerometer, finding that the phases of the winds agree very well but CHAMP wind values at high latitudes are typically 1.5–2 times larger than FPI winds.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the GOCE measured wind generally correlates well with the other observations on the dawn side, but relatively larger discrepancies are found on the dusk side. Aruliah et al (2019) compared high-latitude thermospheric winds measured by two ground-based FPIs and CHAMP accelerometer, finding that the phases of the winds agree very well but CHAMP wind values at high latitudes are typically 1.5-2 times larger than FPI winds.…”
mentioning
confidence: 99%